Advances and lessons learned in co-managed watershed components applied at the upper portion of La Soledad River, at Valle de Angeles County, Honduras - Speer Laínez, William R. (2010)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2010